Methods for Measuring Patient Service Satisfaction in Health Services: Systematic Literature Review - Astuti, Eka Rati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Although attention to patient-centered services continues to increase, unfortunately, in-depth research on the standardization and adaptation of patient satisfaction measurement instruments in the context of healthcare facilities remains limited. Many studies have focused on general satisfaction levels but have lack depth in capturing dimensions such as emotional engagement, cultural expectations, and service delivery across diverse health systems. The purpose of this discussion is to determine appropriate methods for measuring patient service satisfaction in the health sector. Method: This study employed a systematic literature review approach to identify, analyze, and synthesize existing research related to methods for measuring patient service satisfaction in health services. The review process adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines to ensure methodological transparency and rigor. The results: showed that tools such as the SERVQUAL, HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems), and PSQ-18 (Patient Satisfaction Questionnaire Short Form) often failed to capture culturally specific expectations and emotional dimensions of patient experience Conclusion: The importance of using appropriate methods to measure patient service satisfaction in the health sector lies in selecting tools that align with the context and objectives of the measuring the satisfaction includes SERVQUAL, HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems), and PSQ-18 (Patient Satisfaction Questionnaire Short Form).